A summary of modeling studies of the Krafla Geothermal Field,Iceland - Bodvarsson, Gudmundur S.; Pruess, Karsten; Stefansson, Valgardur; Eliasson, Einar T. (Lawrence Berkeley National Laboratory, 1983)
A comprehensive modeling study of the Krafla geothermalfield in Iceland has been carried out. The study consists of four tasks:the analysis of well test data, modeling of the natural state of summaryof the the field, the determination of the generating capability of thefield, and modeling of well performance. The results of all four tasksare consistent with field observation.